Halophytes: Potential Resources for Salt Stress Tolerance Genes and Promoters - Mishra, Avinash; Tanna, Bhakti (Frontiers in Plant Science, 2017)
Halophytes have demonstrated their capability to thrive under extremely saline conditions and thus considered as one of the best germplasm for saline agriculture. Salinity is a worldwide problem, and the salt-affected areas are increasing day-by-day because of scanty rainfall, poor irrigation system, salt ingression, water contamination and other environmental factors. The salinity stress tolerance mechanism is a very complex phenomenon, and some pathways are coordinately linked for imparting salinity tolerance. Though a number of salt responsive genes have been reported from the halophytes, there is always a quest for promising stress-responsive genes that can modulate plant physiology according to the salt stress. Halophytes such as Aeluropus, Mesembryanthemum, Suaeda, Atriplex, Thellungiella, Cakile and Salicornia serve as a potential candidate for the salt-responsive genes and promoters. Several known genes like antiporters (NHX, SOS, HKT, VTPase), ion channels (Cl-, Ca2+, aquaporins), antioxidant encoding genes (APX, CAT, GST, BADH, SOD) and some novel genes such as USP, SDR1, SRP etc. were isolated from halophytes and explored for developing stress tolerance in the crop plants (glycophytes). It is evidenced that stress triggers salt sensors that lead to the activation of stress tolerance mechanisms which involve multiple signaling proteins, up- or down- regulation of several genes, and finally the distinctive or collective effects of stress-responsive genes. In this review, halophytes are discussed as an excellent platform for salt responsive genes which can be utilized for developing salinity tolerance in crop plants through genetic engineering.